A randomised controlled trial comparing the effects of honey versus sucrose as an analgesia during routine venepuncture in newborns - Khanisa, Md Khalid (2011)
A Randomised Control Trial comparing the effects of Honey versus Sucrose as analgesia during routine venepuncture in newbom To dctennine the effectiveness and short term side effects of honey as analgesia in comparison to sucrose during routine venepuncture in newborn. A total of 78 tenn neonates were recmited from the Neonatal Intensive Care Unit and Special Care Nursery of Hospital Universiti Sains Malaysia. These neonates were randomized into two equal sized group receiving either 2 ml of oral 24% sucrose or 2 ml of Tualang honey 2 minutes prior to venepuncture. The whole procedure was videotaped. The degree of pain score using PIPP and duration of crying time were determined twice by two independent observer. The Mann Whitney U test was used to compare the pain scores and duration of cry between the study groups while the Wilcoxon sign rank test was used to compare differences within each group. The result showed no significant differences in the demographic characteristics of the neonates. The median values of PIPP at 30 seconds and 150 seconds were comparable (p value = 0.871) between both groups (median PIPP sucrose = 5, 3 median PIPP for honey = 5, 2 respectively). The median PIPP score within each group was significantly higher (p value= 0.00) at 30 seconds (median =5) compared to at 150 seconds (median = 2.5). The duration of audible cry after venepuncture was not statistically significant {p=0.803) in neonates receiving honey (median= 5.5 seconds) compared to neonates receiving 24% sucrose (median = 4 seconds). No neonates developed hyperglycemia, diarrhea or glycosuria in this study. The result showed no significant differences in the demographic characteristics of the neonates. The median values of PIPP at 30 seconds and 150 seconds were comparable (p value = 0.871) between both groups (median PIPP sucrose = 5, 3 median PIPP for honey = 5, 2 respectively). The median PIPP score within each group was significantly higher (p value= 0.00) at 30 seconds (median =5) compared to at 150 seconds (median = 2.5). The duration of audible cry after venepuncture was not statistically significant {p=0.803) in neonates receiving honey (median= 5.5 seconds) compared to neonates receiving 24% sucrose (median = 4 seconds). No neonates developed hyperglycemia, diarrhea or glycosuria in this study.